European Cultural and Touristic Heritage: Sighisoara vs. Verona - Irina-Virginia Dragulanescu; Gabriela Cecilia Stanciulescu; Ion Andrei; Timea-Anca Stan (Amfiteatru Economic Journal, 2014)
Europe is one of the world's regions with the largest concentration of heritage sites and is also the top tourist destination in the world. Even if every European country has a unique and valuable cultural endowment, the socio-economic evolution of each country led to differences in their development stage. The hereby paper aims to highlight the importance of touristic activities in the sustainable development of a touristic area with the help of a specific form of tourism based on the cultural and historical assets. The two heritage cities chosen for this study are Sighisoara (Romania) and Verona (Italy), both enrolled to the World Heritage List based on their outstanding historical and architectural value. By using qualitative research methods like the observation and the comparison, but also the analysis of statistic data regarding the tourist floe in the chosen destinations, this paper tries to enhance the possibility of partnership between Sighisoara and Verona based on their comparable medieval and cultural features, highlighting the importance of destination management know-how exchange and the added value of these heritage cities. The purpose of this paper is to analyze the tourism potential of both cities, but also the problems they face regarding in from of the short length of tourist stay, coming with a possible solution of joint destination branding of the two cities and the proposal for two thematic travel packages designed to promote them on the European market.
Keywords: M31; L83; 330; thematic tourism; cultural heritage; historic and architectural value; partnership